THE EFFECT OF QUALITY OF WORK LIFE ON JOB EMBEDDEDNESS MEDIATED BY ORGANIZATIONAL COMMITMENT IN GOVERNMENT INSTITUTIONS - Vilya Al-Wirya Mentari (Pena Cendekia Insani, 2026)
The increasing tendency of Civil Servants to transfer between institutions or work units reflects a low level of employee attachment to the organization. This condition highlights the importance of job embeddedness in supporting the sustainability of organizational performance. This study aimed to examine the effect of quality of work life on job embeddedness mediated by organizational commitment within a government institution. The research employed a quantitative approach with an explanatory design. The population consisted of all functional and administrative Civil Servants in one work unit of a government institution, totaling 324 employees, using a saturated sampling technique. Data were collected using job embeddedness, quality of work life, and organizational commitment scales and analyzed using Structural Equation Modeling (SEM). The results indicate that quality of work life has a positive and significant effect on organizational commitment and job embeddedness, while organizational commitment has a positive effect on job embeddedness and serves as a mediating variable. This study demonstrates that improving quality of work life can strengthen organizational commitment and enhance Civil Servants attachment to their organization.